Class-A scavenger receptor function and expression in the rainbow trout (Oncorhynchus mykiss) epithelial cell lines RTgutGC and RTgill-W1. Issue 1 (May 2015) - Poynter, Sarah J.; Weleff, Jeremy; Soares, Adam B.; DeWitte-Orr, Stephanie J.
Abstract Class A scavenger receptors (SR-As) are cell surface receptors that bind a range of ligands, including modified low-density lipoproteins (mLDLs) and nucleic acids. Due to their ability to bind extracellular dsRNA, SR-As play an important role in the viral dsRNA initiated immune pathway. Most research on SR-As has focused on mammalian models, and there has been limited research on SR-As in fish. Thus, the presence of functional class A scavenger receptors (SR-As) were investigated in the rainbow trout cell lines, RTgutGC and RTgill-W1. SR-A ligand binding was assessed using fluorescently labeled acetylated-low density lipoprotein (acLDL) and synthetic dsRNA, polyinosinic:polycytidylic acid (poly IC), in combination with a series of known SR-A competitive ligands: fucoidan, dextran sulfate (DxSO4) and polyinosinic acid (poly I). Both cell lines were able to bind acLDL, which was blocked by SR-A competitive ligands. In RTgutGC, acLDL and poly IC competed for binding to the same surface receptor; however, in RTgill-W1 they did not. Poly IC-fluorescein binding was blocked by SR-A competitive ligands in RTgutGC but not RTgill-W1, suggesting an SR-A dependent dsRNA uptake mechanism in RTgutGC and an SR-A-independent update mechanism in RTgill-W1. Both cell lines responded to extracellular dsRNA treatment with the up-regulation of interferons (IFNs) and interferon stimulated genes (ISGs) as measured by quantitative (q)RT-PCR; however, RTgutGC expressed significantly higher transcript levels for both IFNs and ISGs compared with RTgill-W1 following extracellular poly IC treatment. Expression of SR-As, specifically a SCARA4-like sequence, was identified at the transcript level in both cell lines. These results suggest that both RTgill-W1 and RTgutGC express functional SR-As that are able to bind the classic SR-A ligand, acLDL. Although they both express SCARA4, the full SR-A expression profile; however, is likely different between the cell lines, as dsRNA uptake appears to be SR-A dependent in RTgutGC but SR-A-independent in RTgill-W1. Also, dsRNA uptake via SR-As appears to mediate a more robust antiviral response compared with a SR-A independent method of uptake. This study is the first to identify functional SR-As in rainbow trout epithelial cells, and contributes not only to a better understanding of modified LDL transport but also innate immunity in these economically important animals.